4x-3(x-1)=-2+4x+8

Simple and best practice solution for 4x-3(x-1)=-2+4x+8 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4x-3(x-1)=-2+4x+8 equation:


Simplifying
4x + -3(x + -1) = -2 + 4x + 8

Reorder the terms:
4x + -3(-1 + x) = -2 + 4x + 8
4x + (-1 * -3 + x * -3) = -2 + 4x + 8
4x + (3 + -3x) = -2 + 4x + 8

Reorder the terms:
3 + 4x + -3x = -2 + 4x + 8

Combine like terms: 4x + -3x = 1x
3 + 1x = -2 + 4x + 8

Reorder the terms:
3 + 1x = -2 + 8 + 4x

Combine like terms: -2 + 8 = 6
3 + 1x = 6 + 4x

Solving
3 + 1x = 6 + 4x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-4x' to each side of the equation.
3 + 1x + -4x = 6 + 4x + -4x

Combine like terms: 1x + -4x = -3x
3 + -3x = 6 + 4x + -4x

Combine like terms: 4x + -4x = 0
3 + -3x = 6 + 0
3 + -3x = 6

Add '-3' to each side of the equation.
3 + -3 + -3x = 6 + -3

Combine like terms: 3 + -3 = 0
0 + -3x = 6 + -3
-3x = 6 + -3

Combine like terms: 6 + -3 = 3
-3x = 3

Divide each side by '-3'.
x = -1

Simplifying
x = -1

See similar equations:

| x(4)+y(3)=99 | | -6(6k+7)=2k-4 | | 9b-3=-30 | | 27+3a=3(a+8) | | 6x-7+7x=123 | | 23q-14=56q-80 | | -110=10(-5+n) | | ex=11 | | 11x-3=2x+4 | | 11x-3=2x+5 | | 3-x/8=5x/2-2/3*(x-4)+5 | | 16x-2=5(3x+3)-13 | | 11-8x=-37 | | X=-8y-3 | | 10x+26(x-2)=416 | | 1=9-11+5 | | 25b^2+70bg+49g^2= | | 9x-27=-6x+4 | | 5y-9y=-12-16 | | (74+86)2=81 | | 8x+28-3=9x+15 | | 14+7(z+2)=6z+1 | | sin^2(2x)+3sin^2(x)=3 | | -10(x+5)+70=15-15 | | 14(x+3)-2x=3(4x+1)-7 | | 4/5*(n-10)=-8/9 | | 4/5*(n-10)=-89 | | 6y-7=4y+5 | | -4+11=14x-5-13x | | 63x+25x=300+25x | | 5-b=29 | | -6x+2x-9x= |

Equations solver categories